2014
DOI: 10.1016/j.jagp.2013.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Brain Stimulation in the Treatment of Late-Life Severe Mental Illness Other than Unipolar Nonpsychotic Depression

Abstract: Late-life mental illness is a growing concern. Current medications have limited efficacy and are associated with safety concerns. A variety of brain stimulation approaches offer alternative treatments. We performed a systematic literature search on the efficacy and safety of brain stimulation in late-life mental illnesses, excluding unipolar non-psychotic depression. Studies on deep brain stimulation (DBS), electroconvulsive therapy (ECT), repetitive transcranial magnetic stimulation (rTMS), and vagal nerve st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…The microstructural and functional connectivity findings are consistent with the hypothesis of imbalanced integration of internal memory and external visual input (Diederich et al 2005 ; Goetz 2009 ) which contribute to visual hallucinations in Parkinson’s disease, and implicating that this pathological phenomenon can be underlied by the microstructural deficit and dysfunction in hippocampus. The consistent result of the hippocampal biomarker indicated in the present study supports future development of therapeutic strategy on the basis of neuro-guided stimulation approach, such as transcranial magnetic stimulation (TMS) (Liu et al 2013 ) and transcranial direct current stimulation (tDCS) (Brunoni et al 2013 ) to modulate the connectivity strength of visual networks.…”
Section: Discussionsupporting
confidence: 84%
“…The microstructural and functional connectivity findings are consistent with the hypothesis of imbalanced integration of internal memory and external visual input (Diederich et al 2005 ; Goetz 2009 ) which contribute to visual hallucinations in Parkinson’s disease, and implicating that this pathological phenomenon can be underlied by the microstructural deficit and dysfunction in hippocampus. The consistent result of the hippocampal biomarker indicated in the present study supports future development of therapeutic strategy on the basis of neuro-guided stimulation approach, such as transcranial magnetic stimulation (TMS) (Liu et al 2013 ) and transcranial direct current stimulation (tDCS) (Brunoni et al 2013 ) to modulate the connectivity strength of visual networks.…”
Section: Discussionsupporting
confidence: 84%
“…It has been proposed that potential pro-cognitive effects of DBS may be enhanced by combining stimulation with another intervention, such as cognitive remediation [64]. …”
Section: Treatmentmentioning
confidence: 99%
“…16 Rare serious AE (<1%) are seizures and induction of hypomania, hearing changes and burns from the coil. 4,14,[17][18][19][20][21] Most often, people aged over 60 are excluded from trials. The National Institute for Health Care Excellence (NICE)-guideline of rTMS for depression is based on studies with a mean age between 38.4 and 50.5 years, the remaining studies used in the NICE-guideline did not mention a mean age.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the tolerability of rTMS in adults has reported several AE such as headache (9.7%), local pain and discomfort (9.3%), and neck pain, toothache, and paresthesia (together 4.7%) 16 . Rare serious AE (<1%) are seizures and induction of hypomania, hearing changes and burns from the coil 4,14,17‐21 …”
Section: Introductionmentioning
confidence: 99%